Chitosan/guargum-g-acrylamide semi IPN microspheres for controlled release studies of 5-Fluorouracil - E. Chandra Sekhar, K.S.V. Krishna Rao, R. Ramesh Raju (Journal of Applied Pharmaceutical Science)
Chitosan and guargum-gt-acrylamide (CH-GG-g-AAm) semi interpenetrating microspheres (semi IPNMs) were prepared by water-in-oil (w/o) emulsion cross linking method using glutaraldehyde as a crosslinker. 5-fluorouracil (5-FU) is an anticancer drug was successfully loaded in these semi IPNMs. X-ray diffraction (XRD) and differential scanning calorimetric (DSC) examined the crystalline nature of drug after encapsulation into semi IPNMs. Scanning electron microscopy (SEM) shows the formation of semi IPNMs is spherical with size around 200 ??m. The encapsulation efficiency of 5-FU was achieved 58%. In-vitro release studies were performed basic (pH 7.4) buffer medium. The release patterns depend on graft polymer composition, effect of cross linker and drug content in the polymer matrices. In vitro release studies indicated the release of 5- FU more than 12 hours.